The Histone Methyltransferase Ezh2 Controls Mechanisms of Adaptive Resistance to Tumor Immunotherapy - Zingg, Daniel; Arenas-Ramirez, Natalia; Sahin, Dilara; Rosalia, Rodney A.; Antunes, Ana T.; Haeusel, Jessica; Sommer, Lukas; Boyman, Onur (Cell reports (Cambridge), 2017)
Immunotherapy and particularly immune checkpoint inhibitors have resulted in remarkable clinical responses in patients with immunogenic tumors, although most cancers develop resistance to immunotherapy. The molecular mechanisms of tumor resistance to immunotherapy remain poorly understood. We now show that induction of the histone methyltransferase Ezh2 controls several tumor cell-intrinsic and extrinsic resistance mechanisms. Notably, T cell infiltration selectively correlated with high EZH2-PRC2 complex activity in human skin cutaneous melanoma. During anti-CTLA-4 or IL-2 immunotherapy in mice, intratumoral tumor necrosis factor-α (TNF-α) production and T cell accumulation resulted in increased Ezh2 expression in melanoma cells, which in turn silenced their own immunogenicity and antigen presentation. Ezh2 inactivation reversed this resistance and synergized with anti-CTLA-4 and IL-2 immunotherapy to suppress melanoma growth. These anti-tumor effects depended on intratumorally accumulating interferon-γ (IFN-γ)-producing PD-1low CD8+ T cells and PD-L1 downregulation on melanoma cells. Hence, Ezh2 serves as a molecular switch controlling melanoma escape during T cell-targeting immunotherapies. [Display omitted] •Intratumoral T cells and TNF-α cause Ezh2 upregulation in melanoma cells•Ezh2 silences immunogenicity and antigen presentation in melanoma•Ezh2 blockade reverses melanoma resistance mechanisms•Ezh2 inactivation synergizes with anti-CTLA-4 and IL-2 immunotherapy Zingg et al. investigate the mechanisms of adaptive resistance to tumor immunotherapy. They find that intratumoral TNF-α production and T cell accumulation promote Ezh2 upregulation in melanoma cells, resulting in loss of immunogenicity and antigen presentation. Ezh2 inactivation reverses these effects and synergizes with anti-CTLA-4 and IL-2 immunotherapies.